Effects of Climate Change and Human Activities on Net Primary Productivity in Yunnan Province - Hong XU; Jinxin CHENG; Yuqin HE; Youting WANGYU; Maosong ZHANG (Gaoyuan qixiang)
Net primary productivity（NPP） directly and truly reflected the dynamic changing process of terrestrial vegetation ecosystem.Understanding the driving mechanism of climate change and human activities on vegetation change was of great scientific significance to ecological protection and sustainable development.Based on MOD17A3/NPP product， using linear trend analysis， Mann-Kendall significance analysis， Hurst index and partial correlation analysis， the temporal and spatial distribution characteristics of vegetation NPP in Yunnan Province from 2001 to 2021， the future sustainability and the relationship between vegetation NPP and meteorological conditions were discussed.Residual analysis used to quantitatively assess the relative contributions and combined action of climate change and human activities to the vegetation NPP.The result as follow： （1）Spatially， the annual mean NPP value of Yunnan vegetation from 2001 to 2021 was high in the south and low in the north.The order of values from the high to low was woodland （1106.7 gC∙m-2）， shrub （964.4 gC∙m-2）， agricultural land （946.6 gC∙m-2） and grassland （878.8 gC∙m-2） in different vegetation types.The vegetation NPP increased and then decreased with increasing altitude.（2）During the study period the annual mean vegetation NPP was 1020.8 ± 30.7 gC∙m-2， with minimum and maximum values occurring in 2010 （950.0 gC∙m-2） and 2019 （1062.1 gC∙m-2）， respectively.The vegetation NPP showed a significant increase with an increase rate of 2.1 gC∙m-2∙a-1 （p<0.05）.The increasing and significantly increasing areas accounted for 70.0% and 26.3% of the total area of the study area， respectively.The vegetation NPP of different vegetation types showed a similar variation trend.The increasing rates showed grassland （4.1 gC∙m-2∙a-1）> farmland （3.5 gC∙m-2∙a-1）> shrub （2.8 gC∙m-2∙a-1）>forestland （1.3 gC∙m-2∙a-1）.The average value of the Hurst index was 0.60.The proportion of the area that would continue to increase and change from decrease to increase was 55.5% and 9.3%， respectively.This indicated that the vegetation NPP would continue to increase in most areas in the future.（3）The average temperature in Yunnan Province showed a significant increase from 2001 to 2021， while precipitation and solar radiation showed a fluctuating decrease.These climatic factors positively correlated with vegetation NPP in most areas， and the effect of temperature on vegetation NPP was greater than that of precipitation and solar radiation.（4） The relative contribution rates of climate change and human activities to vegetation NPP change in Yunnan were 27.1% and 72.9%， respectively， with positive contributions accounting for 59.4% and 64.6% of the total area of the study area， and relative contribution rate greater than 60% accounting for 12.7% and 73.4% of the area， respectively.The impact of human activities on vegetation NPP was greater than that of climate change in most areas.The vegetation improvement in Yunnan was mainly caused by the combined effect of climate change and human activities， while the degradation was mainly caused by the human activities and the combined effect.The ecological protection and restoration projects had a significant contribution to the improvement of vegetation NPP in Yunnan.